1988
DOI: 10.1111/j.1471-4159.1988.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemia on the In Vivo Release of Striatal Dopamine, Glutamate, and γ‐Aminobutyric Acid Studied by Intracerebral Microdialysis

Abstract: We have previously described a marked attenuation of postischemic striatal neuronal death by prior substantia nigra (SN) lesioning. The present study was carried out to evaluate whether the protective effect of the lesion involves changes in the degree of local cerebral blood flow (ICBF) reduction, energy metabolite depletion, or alterations in the extracellular release of striatal dopamine (DA), glutamate (Glu), or gamma-aminobutyric acid (GABA). Control and SN-lesioned rats were subjected to 20 min of forebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
237
1
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 706 publications
(262 citation statements)
references
References 53 publications
21
237
1
3
Order By: Relevance
“…2 Thus, modulation of K + channel activity has been acknowledged as a possible target for neuroprotection. Among the different neurotransmitters, dopamine release has been shown to reach very high levels soon after an ischemic insult in the caudate, and also to contribute to neuronal damage; 5 indeed, depletion of dopaminergic nigro-striatal projections has been shown to reduce ischemic damage. 19 Dopamine and related compound such as L-3,4-dihydroxyphenylalanine and 6-OH-DOPA are considered as potent excitotoxic agents, possibly contributing to neurodegeneration in Parkinson's and Huntington's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, modulation of K + channel activity has been acknowledged as a possible target for neuroprotection. Among the different neurotransmitters, dopamine release has been shown to reach very high levels soon after an ischemic insult in the caudate, and also to contribute to neuronal damage; 5 indeed, depletion of dopaminergic nigro-striatal projections has been shown to reduce ischemic damage. 19 Dopamine and related compound such as L-3,4-dihydroxyphenylalanine and 6-OH-DOPA are considered as potent excitotoxic agents, possibly contributing to neurodegeneration in Parkinson's and Huntington's disease.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although glutamate release has been viewed as a main cause of neuronal damage, massive release of monoamines, such as dopamine, also occurring immediately after the onset of ischemia, can be neurotoxic and thus contribute to cell death. 5 Moreover, it has been shown that chronic methamphetamine administration as well as striatal injection of dopamine caused a marked presynaptic and postsynaptic neuronal death in rodents. 6 Dopamine release during ischemia is supposed to be a consequence of different mechanisms, such as cell depolarization, reversal of dopamine transporters, and ATP shortage.…”
Section: Introductionmentioning
confidence: 99%
“…This index was first used to describe the imbalance between excitatory and inhibitory processes at the neuronal level, where brain concentrations of glutamate and glycine, and the inhibitory amino acid gamma-aminobutyrate (GABA) were measured in rats subjected to transient global ischemia. 10 This index is intended to provide an overall assessment regarding the state of excitotoxicity and is thus a measure of neural imbalance. Under basal conditions the index would display homeostasis between excitatory and inhibitory processes.…”
Section: Excitotoxicitymentioning
confidence: 99%
“…The age related difference in increase in taurine might be based on regional nature because the magnitude of the increase in SHR during ischemia was smaller (-lO-fold) in the striatum of both adult and aged SHR compared with that in the hippocampus (16-to 26-fold). The vulnerability of the hippocampus to ischemia is likely to be more closely related to ex citotoxicity than that of the striatum (Globus et al , 1988;Benveniste et al , 1990) as is that of the cere bral cortex (Park et al , 1988). As for the other amino acids in this study, viz., glutamine, alanine, glycine plus threonine, and GABA, there were no differences in the changes in extracellular concentrations between the groups.…”
Section: Discussionmentioning
confidence: 85%